PENGARUH PENGETAHUAN-SIKAP MENGENAI VITAMIN D TERKAIT OBESITAS PADA MAHASISWA - Amelia Lorensia; Dian Natasya Raharjo; Novelia Gandawari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Indonesia as a tropical country has a tendency to experience vitamin D deficiency. Knowledge and attitudes towards sun exposure contribute to the risk of vitamin D deficiency. In the midst of urban life patterns, obesity also increases the risk of vitamin D deficiency. This study was conducted to determine the effect of the level of knowledge and attitudes regarding vitamin D related to obesity in adults, which was conducted in March 2018 to January 2019. The study used a cross sectional design, with a knowledge and attitude questionnaire regarding vitamin D. Respondents were adults and domiciled in Surabaya , as many as 74 people in each group of obesity and non-obese. The results showed that obese and non-obese respondents both had good knowledge (OR 1.138) but had a bad attitude (OR 1,000). There was no significant difference in knowledge and attitudes in the two groups, and had a weak correlation.